STUDI META ANALISIS TENTANG HUBUNGAN WORK-LIFE BALANCE, PERCEIVED ORGANIZATION SUPPORT, & COACHING TERHADAP JOB PERFORMANCE - Salim, Felia Levina; Nawangsari, Hana Citra Putri; Ratyadewi, Pande Made Kintan; Suryanata, Sherina (Universitas Wiralodra, 2025)
The purpose of the current literature review is to (a) provide a comprehensive understanding of the relationship between work life balance, perceived organizational support, coaching and job performance with employee engagement as mediating variable; (b) construct an integrated conceptual framework based on empirically validated factors and their relationships, along with relevant theories. An integrative literature review of 12 empirical studies indicates that work-life balance, perceived organizational support, coaching and employee engagement has a significant positive effect on job performance. The findings also indicate that work-life balance, perceived organizational support, coaching indirectly significantly influence the job performance through the mediating role of employee engagement.